STRATEGI KOMUNIKASI DALAM MENGIMPLEMENTASI KEGIATAN CSR (STUDI KASUS PADA PROGRAM KEMITRAAN DAN BINA LINGKUNGAN TERHADAP MITRA BINAAN PT SIER) - Nuriyah, Tika Nadhifatun; Setianingrum, Vinda Maya (Universitas Negeri Surabaya, 2024)
PKBL was a mandatory social responsibility program of PT SIER, regulated by the Minister of State-Owned Enterprises Regulation Number PER-05/MBU/2007. This research aimed to describe the communication strategies implemented in the execution of the partnership program held by the TJSL Department of PT SIER. The research method used was a case study with a qualitative approach. The data collected by the researcher came from semi-participant observations, interviews with company employees and partner beneficiaries, as well as through company documents and documentation. The research results showed that PKBL was a corporate social responsibility based on the CSR Triple Bottom Line principle. PT SIER strived to achieve a balance between economic performance (Profit), community social development (People), and green industrial area management (Planet). The factors influencing the success of PKBL implementation were impacted by the communication strategies of the TJSL Department to partner beneficiaries. The communication strategies used began with identifying the audience, determining the objectives, crafting the messages, and establishing the methods or media.